Hypervalent iodine compounds: synthesis, structure and its applications in aqueous media - Mironova I. A. Irina Andreevna; Izosimova K. M. Kristina Mikhaylovna; Kartashov I. A.; Shurikov M. K. Matvey Konstantinovich; Chumerin D. S.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (Химия и химическая технология на иностранном языке, 2020)
Заглавие с экрана